Microsurgery in endodontics - Kim, Syngcuk; Kratchman, Samuel; Karabucak, Bekir; Kohli, Meetu; Setzer, Frank (Chichester, West Sussex : Wiley Blackwell, 2017)
Microsurgery in Endodontics provides the definitive reference to endodontic microsurgery, with instructive photographs and illustrations.-Provides a definitive reference work on endodontic microsurgery -Includes contributions from pioneers and innovators in the field of microsurgical endodontics -Describes techniques for a wide range of microsurgical procedures -Includes more than 600 instructive illustrations and photographs.
Includes bibliographical references and index.
CIP data; resource not viewed.
Keywords: Dental pulp -- Surgery; Microsurgery; MEDICAL -- Dentistry -- General; Dental pulp -- Surgery; Microsurgery; Electronic books